Edukasi Pembuatan Gula Semut Sebagai Pemanis Alami: Pemanfaatan untuk Meningkatkan Literasi Pangan Sehat - Pratama, Desta Ayu; Aryani, Vina Dinata Kamila; Zukryandry, Zukryandry; Safitri, Bella Intan Ayu; Shabrina, Astri; Samosir, Joni Frengki; Khoerunnisa, Tiara Kurnia (JPM: Jurnal Pengabdian Masyarakat, 2026)
The high consumption of refined sugar in Indonesia increases the risk of non-communicable diseases, such as obesity, diabetes, and hypertension. Education on healthier natural sweeteners, like palm sugar, is needed to improve public food literacy. Palm sugar, derived from coconut or palm sap, contains minerals (potassium, magnesium, iron) and has a lower glycemic index compared to refined sugar, making it a potential alternative natural sweetener. This community service aimed to increase public knowledge of palm sugar's nutritional benefits and encourage behavioral change to reduce refined sugar consumption. The participatory learning and action (PLA) method was used, consisting of preparation, education, and evaluation stages. Education included interactive lectures, demonstrations, and group discussions. Evaluation was done with pre-test and post-test questionnaires and observation of interest in palm sugar use. Results showed a 56.7% increase in participants' knowledge after the education. Most participants also expressed willingness to replace refined sugar with palm sugar in their daily diet.